2015
DOI: 10.1115/1.4030488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trailing-Edge Modification of a Mixed-Flow Pump

Abstract: Modern pumps are designed to guarantee a sufficiently large operating range or to satisfy the performance requirements relative to more than one operating point. This study applies trailing-edge (TE) modification method based on TE rounding in the suction surface to widen the operating range of a mixed-flow pump. The effects of TE modification on the performance and internal flow of the mixed-flow pump are investigated through computational fluid dynamics (CFD) analysis. Local Euler head distribution is introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 17 publications
4
25
0
Order By: Relevance
“…Al-Qutub et al [19] assessed the influences of V-shaped trailing edge on the unstable pressure pulsation of centrifugal pump and concluded that the V-shaped trailing edge can effectively reduce the pressure pulsation intensity inside the centrifugal pump. Wu et al [20] explored the influences of different fillet radii of blade trailing edge on the internal flow of mixed flow pump. They believed that the trailing edge with large radius could effectively improve the speed distribution of the impeller outlet.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Qutub et al [19] assessed the influences of V-shaped trailing edge on the unstable pressure pulsation of centrifugal pump and concluded that the V-shaped trailing edge can effectively reduce the pressure pulsation intensity inside the centrifugal pump. Wu et al [20] explored the influences of different fillet radii of blade trailing edge on the internal flow of mixed flow pump. They believed that the trailing edge with large radius could effectively improve the speed distribution of the impeller outlet.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these works focus on the core component of the pump, e.g. the impeller [3][4]. Influences of various structural parameters of the impeller on flow characteristics of the pump are studied, including the blade angle, the wrap angle, the impeller diameter, the inlet/outlet width, the blade fillet, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Houlin et al 8 presented the multicondition optimisation for a centrifugal pump impeller on the basis of an adaptive simulated annealing algorithm. In the design procedure, several geometrical parameters, such as the impeller trimming, 9 flow passage shape, 10 blade wrap angle, 11 blade trailing edge 12 and blade outlet angle, 13 exhibit an important effect on pump performance. Except for the impeller itself, an effective way to improve the energy performance is the flow guiding device of guide vanes.…”
Section: Introductionmentioning
confidence: 99%